Elite Delights: The Structure of Art Gallery Networks in India - Olivier Roueff (South Asia Multidisciplinary Academic Journal)
In recent years, researchers have expressed renewed interest in the visual arts, which can be seen as one of the main providers of upper-class symbolic goods and status signals for cultural elites. India has not yet been included in that body of work. Although important insights do exist on India, a systematic empirical inquiry has yet to be made. The present article offers a step in that direction, through the statistical analysis of 101 Indian galleries and the 4,249 artists they present in their catalogs. Does the way galleries share artists reveal specific characteristics about the Indian art world? Is the usual opposition between “commercial” and “artistic” galleries relevant for contemporary India? What are the roles of auctions and international fairs? Do Indian galleries prefer representing artists, or storing and exhibiting their works? What insights do their strategies and hierarchies offer about the cultural standards of Indian elites? This article offers a typology of Indian art galleries based on a network analysis (blockmodeling). It reveals a hierarchized system, the weight of the auction market, and a strong economic and aesthetic boundary between international experimental art and national modern art.